Mixed Ligand Ni(II) Complexes of Isonitroso-β-Ketoimines, β-Ketoimines and Salicylaldimines and Some of Their Reactions; Importance of H-Bonding in the Stabilization of Isonitroso N-Bonded Isomer. - BALASUBRAMANIAN, V.; LOGANAYAGI M. MUNEESWARAN, A.; DURAI , V. (Asian Journal of Chemistry, 2010)
A new series of diamagnetic nickel(II) complexes of isonitroso-β- ketoimines, β-ketoimines and salicylaldimines have been synthesised and characterised by analytical, IR, NMR, CMR and electronic spectral studies. Synthesis of this type of complexes has been achieved by chelate exchange method. The quasiaromatic character of acetylacetoneimine moiety of mixed ligand complexes is confirmed by conducting nitrosation, bromination and phenyl isocyanation and the products have been characterised by elemental analyses, electronic and IR studies.